The traditional belief system in relation to mental health and psychiatric services in Sudan - Sorketti, E.A.; Zuraida, N.Z.; Habil, M.H. (Royal College of Psychiatrists UK, 2012)
Traditional healers’ centres may constitute community resources for people with a mental illness. Traditional healers often have the respect of the population they serve. Many low-income countries are seeking to integrate mental health into their mainstream health services and primary healthcare, so as to decrease the duration of untreated mental illness. Traditional healers can help to meet these needs. A series of four studies has been conducted in central Sudan. In-patients with mental disorders undergoing treatment with traditional healers were recruited, as well as some of the healers themselves. The resulting observations should help practitioners trained in ‘Western’ psychiatry to better understand traditional healing as an alternative healthcare system. The results should contribute to current debates on whether or not traditional healers in Africa should be officially recognised as healthcare providers. They should also deepen social scientists’ understanding of the role of culture in mental health and help policy-makers to improve mental health services.